CREATIVE EMBROIDERY & BEYOND tips, inspiration, techniques, & projects from professional artists - Billingham, Jenny; Timms, Sophie; Wensing, Theresa (WALTER FOSTER PUB, 2023)
From the best-selling Creative...and Beyond series, Creative Embroidery & Beyond presents beautiful embroidery projects and instruction for all skill levels from three trending artists.